Engineering Ribosomes to Alleviate Abiotic Stress in Plants: A Perspective - Leticia Dias-Fields; Katarzyna P. Adamala (Plants, 2022)
As the centerpiece of the biomass production process, ribosome activity is highly coordinated with environmental cues. Findings revealing ribosome subgroups responsive to adverse conditions suggest this tight coordination may be grounded in the induction of variant ribosome compositions and the differential translation outcomes they might produce. In this perspective, we go through the literature linking ribosome heterogeneity to plants’ abiotic stress response. Once unraveled, this crosstalk may serve as the foundation of novel strategies to custom cultivars tolerant to challenging environments without the yield penalty.